2012
DOI: 10.5009/gnl.2012.6.1.58
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility and Safety of the Endoscopic Submucosal Dissection of Superfi cial Gastric Neoplastic Lesions in Patients with Compensated Liver Cirrhosis: A Retrospective Study

Abstract: Background/AimsWhen undergoing endoscopic submucosal dissection (ESD), patients with liver cirrhosis (LC) may suffer from a high risk of bleeding, bacteremia and tissue vulnerability. There have been few reports evaluating the efficacy and safety of ESD in patients with LC.MethodsFrom January 2004 to March 2010, 23 patients with LC (cirrhosis group) underwent ESD for superficial gastric neoplastic lesions. The number of patients with a liver function in the Child-Pugh classes A and B were 20 and 3, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 27 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…LC severity was classified into categories of CP class A to C, based on each patient’s CP score (CP-A, 5–6 points; CP-B, 7–9 points; CP-C, 10–15 points). 19 This study adhered to the tenets of the Declaration of Helsinki. As the study did not include personal identifiers and was of a retrospective observational nature, informed consent was waived, and the study protocol was approved by the Seoul National University Hospital Institutional Review Board (IRB number: H-1807-042-957).…”
Section: Methodsmentioning
confidence: 99%
“…LC severity was classified into categories of CP class A to C, based on each patient’s CP score (CP-A, 5–6 points; CP-B, 7–9 points; CP-C, 10–15 points). 19 This study adhered to the tenets of the Declaration of Helsinki. As the study did not include personal identifiers and was of a retrospective observational nature, informed consent was waived, and the study protocol was approved by the Seoul National University Hospital Institutional Review Board (IRB number: H-1807-042-957).…”
Section: Methodsmentioning
confidence: 99%
“…However, another study reported that the Child–Pugh score was an independent risk factor for bleeding during colonoscopic polypectomy and that the risk of immediate bleeding after polypectomy was high for patients with cirrhosis in the Child B and Child C groups [ 15 ]. Several studies on the upper gastrointestinal tract in cirrhotic patients have reported various bleeding rates during endoscopic submucosal dissection procedures, ranging from 4.3% to 16.7% [ 16 , 17 , 18 ]. It is not easy to determine the safety issues associated with endoscopic procedures in patients with cirrhosis.…”
Section: Introductionmentioning
confidence: 99%